How Will the Changeover to Digital Broadcasting in 2009 Influence the Accessibility of TV for Americans With Disabilities? - Pedlow, Robert (Disability Studies Quarterly, 2008)
The current paper reports on the numbers of people with disability expected to experience difficulty in accessing television as a result of the planned changeover from analogue to digital broadcasting in the US in 2009. The major accessibility issues for digital TV are reviewed focusing on digital set-top boxes that are expected to be the primary means of access to digital TV for people on low incomes. The changeover to digital TV will reduce the ease of access to broadcast TV for people with disability. As broadcast TV is mostly relied on by people on low income people with disability on low incomes will be at increased risk of exclusion due to the changeover. Older people with disability especially those aging into disability are less likely to access disability information or have connections with the disability community compared to the younger disabled and as a result may be at greater risk of being excluded.